2022
DOI: 10.3389/fimmu.2022.970909
|View full text |Cite
|
Sign up to set email alerts
|

Primitive genotypic characteristics in umbilical cord neutrophils identified by single-cell transcriptome profiling and functional prediction

Abstract: The function and heterogeneity of neutrophils in neonatal umbilical cord blood (UCB) have not been characterized. In this study, we analyzed the neutrophils in UCB and healthy adults using single-cell RNA sequencing analysis for the first time. We found that neutrophils divided into six subpopulations (G2, G3, G4, G5a, G5b, and G5c) with different marker genes and different functions under homeostasis. Compared with healthy adults, neutrophils of UCB were more naïve and have more obvious degranulation and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Based on several clusters enriched in pathway neutrophils activation, we did find that neutrophils increased significantly at the same time. We divided neutrophils into four clusters and found that these four clusters can correspond to the neutrophils in Chen and Xie et al’s scRNA-seq studies 38 , 39 , which further verified the phenotype of neutrophils in the human body. In addition, according to a widely used previous classification scheme, macrophages were grouped into pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Based on several clusters enriched in pathway neutrophils activation, we did find that neutrophils increased significantly at the same time. We divided neutrophils into four clusters and found that these four clusters can correspond to the neutrophils in Chen and Xie et al’s scRNA-seq studies 38 , 39 , which further verified the phenotype of neutrophils in the human body. In addition, according to a widely used previous classification scheme, macrophages were grouped into pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes.…”
Section: Discussionsupporting
confidence: 64%
“…Correlation analysis showed Neutrophils4 were different from any subpopulation of G0–G5. However, according to the known neutrophil typing markers provided by Chen et al 39 , we suggested that Neutrophils4 had the characteristics of G5c (Fig. 5i , Supplementary Data 1 ).…”
Section: Resultsmentioning
confidence: 73%
“…Based on several clusters enriched in pathway neutrophils activation, we did nd that neutrophils increased signi cantly at the same time. We divided neutrophils into four clusters and found that these four clusters can correspond to the neutrophils in Chen and Xie et al's single cell RNA sequencing studies 38,39 , which further veri ed the phenotype of neutrophils in the human body. In addition, according to a widely used previous classi cation scheme, macrophages were grouped into pro-in ammatory (M1) and an anti-in ammatory (M2) phenotypes.…”
Section: Discussionmentioning
confidence: 59%
“…Correlation analysis showed Neutrophils4 were different from any subpopulation of G0-G5. However, according to the known neutrophil typing markers provided by Chen + et al 39 , we suggested that Neutrophils4 were G5c (Fig. 3G).…”
Section: Characterization Of Myeloid Cellsmentioning
confidence: 64%
“… Optional: The high-density cell pellet (which contains non-nucleated red blood cells and high density polymorphonuclear cells, such as granulocytes) can be used for analysis or cryopreserved for later analysis. As our focus in this protocol is on the LDCB fraction, we direct you to additional publications 9 , 10 for these types of analyses. After transferring to new tubes, add 1× PBS so the final volume is approximately 45 mL.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%